Screening of Astec® CHIRALDEXTM G-PN and LIPODEXTM D gas chromatography columns for enantioseparation of amphetamine derivatives - Hubner, Eva-Maria; Schützinger, Sophie; Molnárová, Katarína; Schmid, Martin G (Chirality, 2024)
Among different substance classes, New Psychoactive Substances (NPS) comprise chiral amphetamines for stimulant and empathic effects. There is little knowledge in terms of clinical studies about possibly different effects of the two enantiomers of novel amphetamine derivatives. For this reason, there is a big demand for enantioseparation method development of this new substance class. Regarding gas chromatography, cyclodextrins proved to be effective for enantioseparation of NPS. In our attempt, an Astec® ChiraldexTM G-PN column containing 2,6-di-O-pentyl-3-propionyl-γ-cyclodextrin and a LipodexTM D column containing heptakis-(2,6-di-O-pentyl-O-acetyl)-β-cyclodextrin as chiral selector served as stationary phases in a Shimadzu GCMS-QP2010 SE system. Because of the special coating, maximum temperature is limited to 200 °C isothermal or 220 °C in programmed mode. To ensure detection, trifluoroacetic anhydride (TFAA) was used to increase sample volatility.1 As a result, 35 amphetamines were tested as their TFAA-derivatives. A screening method with a temperature gradient from 140 °C to 200 °C at a heating ramp of 1 °C per minute and final time of 5 min, showed baseline separation for seven and partial separations for 16 trifluoro acetylated amphetamines using the ChiraldexTM G-PN column. Six baseline and nine partial separations were observed with the LipodexTM D column, respectively.
Keywords: teplota; stereoizomerie; Cyclodextrins; Chromatography, Gas; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; amfetaminy; chromatografie plynová; Amphetamines; Temperature; cyklodextriny; Stereoisomerism